Acute toxicity of ammonia and nitrite to Siamese fighting fish (Betta splendens) - Makiko Kajimura; Kazuyuki Takimoto; Ayaka Takimoto (BMC Zoology, 2023)
Abstract The acute toxicity and sublethal effects of ammonia and nitrite on the air-beathing Siamese fighting fish, betta (Betta splendens) was studied for 96 h. The LC50 (50% Lethal Concentration) for 96 h for adult bettas to ammonia-N and nitrite-N was 123.4 mM (1.7 g/L, 95% confidence limits: 114.7–130.0 mM) and 24.6 mM (343.6 mg/L, 95% confidence limits: 22.7–26.4 mM) respectively. Exposure to 90 mM ammonia did not affect ammonia and urea excretion rates in bettas. There was no significant difference in values between control and ammonia-loaded (90 mM ammonia) individuals in either brain or liver activities of glutamine synthase, while plasma ammonia levels slightly increased. It appears unlikely that ammonia was converted to urea or amino acids for detoxification. Sublethal nitrite (24.6 mM nitrite) affected plasma nitrite, methemoglobin and hemoglobin. Plasma nitrite values remained much lower than ambient concentrations. Betta has a labyrinth organ and can breathe air. Bettas may temporarily reduce the entry of ammonia and nitrite into the body by increasing the rate of air respiration and reducing the contribution of the gill epithelium, which is highly permeable to these nitrogenous pollutants.